Differences in expression profiles in malingant melanoma patients according to immunotherapy response - E. N. Lukyanova; M. S. Fedorova; E. A. Pudova; T. V. Nasedkina; E. V. Stepanova; K. M. Nyushko; A. Y. Popov; N. V. Koroban; A. A. Dmitriev; M. V. Kiseleva; A. V. Lipatova; A. S. Zasedatelev; et al. (Вавиловский журнал генетики и селекции)
One of the most important branch of modern molecular genetics and biomedicine is the search for predictive markers that help choose the most effective way of treatment, drug and also determine its individual dosage. Among the markers, those that can provide the possibility of using a noninvasive, socalled “liquid biopsy” are considered particularly promising. This method allows the condition of the tumor to be assessed by analyzing the body’s natural fluids, such as blood, urine or saliva. Such studies are most convenient in those cases when it is necessary to monitor the effectiveness of therapy in order to record the time of the onset of resistance of tumor cells, the onset of relapse and to move on to the next line of therapy. In the treatment of aggressive and rapidly became metastatic malignant tumors, such as melanoma, the presence of reliable markers that allow quick and accurate determination of treatment tactics is especially important. Nowadays, there is an increasing number of studies devoted to the search for predictive markers of the effectiveness of immunotherapy. Melanoma is one of the most immunogenic tumors and, as a result, has become a model object for research into and introduction of new approaches to immunotherapy. In this study, we compared two groups of patients with metastatic skin melanoma, with different responses to immunotherapy with blockers of immune control points, to identify new predictive expression biomarkers among microRNAs and mRNAs, and to identify the genes responsible for the occurrence of an objective response to therapy. As a result, the study detected several microRNAs with a significant change in expression level within the tumor tissue of patients responding differently to immunotherapy. Differences in the level of expression of their target genes have also been found, that will allow a more detailed analysis of the molecular mechanisms that determine the sensitivity or resistance of malignant melanoma cells to the immunotherapy. Based on the obtained data, we have proposed expression markers (mRNAs and microRNAs) that can be used as predictors of malignant melanoma tumors to immunotherapy.